Nonlocal effects in the core ionization and auger spectra of small ammonia clusters - Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2011)
X-ray photoelectron and Auger spectroscopies are well-suited for exploring the chemical state of a selected system. Chemical shifts of electronic transitions and line broadening in the respective spectra contain a wealth of information on the interaction of the core ionized system with its local environment. The presence of neighbors in the vicinity of the core ionized system is responsible for a number of other remarkable effects such as charge-transfer satellites in core ionization spectra and intermolecular electronic transitions in Auger spectra. In addition, due to the environment, some electronic states resulting from Auger decay may further decay electronically via the intermolecular Coulombic decay mechanism. This decay by emission of an electron would be impossible if the core ionized system were isolated. All of the above phenomena happen in the small ammonia clusters whose core ionization and Auger spectra were computed from first principles and are discussed in the present paper.
Gesehen am 11.07.2022